2022
DOI: 10.1111/jeb.14145
|View full text |Cite
|
Sign up to set email alerts
|

Mixed support for an alignment between phenotypic plasticity and genetic differentiation in damselfly wing shape

Abstract: The relationship between genetic differentiation and phenotypic plasticity can provide information on whether plasticity generally facilitates or hinders adaptation to environmental change. Here, we studied wing shape variation in a damselfly (Lestes sponsa) across a latitudinal gradient in Europe that differed in time constraints mediated by photoperiod and temperature. We reared damselflies from northern and southern populations in the laboratory using a reciprocal transplant experiment that simulated time-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…We estimated phenotypic wing shape of wild caught individuals and hence the observed wing shape variation was probably affected by a combination of genetic and environmental effects. In our study species, photoperiod imposes time constraints impacting larval growth, developmental time, and adult morphology [21,23,63,64]. In a recent study, Johansson et al [23] showed that wing shape differences between northern and southern populations of L. sponsa were composed of genetic and plastic responses to photoperiod and temperature in the larval rearing environment.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…We estimated phenotypic wing shape of wild caught individuals and hence the observed wing shape variation was probably affected by a combination of genetic and environmental effects. In our study species, photoperiod imposes time constraints impacting larval growth, developmental time, and adult morphology [21,23,63,64]. In a recent study, Johansson et al [23] showed that wing shape differences between northern and southern populations of L. sponsa were composed of genetic and plastic responses to photoperiod and temperature in the larval rearing environment.…”
Section: Discussionmentioning
confidence: 73%
“…In our study species, photoperiod imposes time constraints impacting larval growth, developmental time, and adult morphology [21,23,63,64]. In a recent study, Johansson et al [23] showed that wing shape differences between northern and southern populations of L. sponsa were composed of genetic and plastic responses to photoperiod and temperature in the larval rearing environment. However, that study [23] was only investigating two populations (north and central), which makes it difficult to compare the observed latitudinal patterns of wing shape to the present study.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…For example, if an organism contains the genetic machinery to be phenotypically plastic in response to a certain environmental variable, it has a larger mutational target size for changing this phenotype. The empirical evidence for this hypothesis is mixed, with some support (Lind et al., 2015 ) and some contradicting results (Johansson et al., 2023 ). Testing this hypothesis would be interesting in the context of priming and antimicrobial resistance.…”
Section: Evolution Of Antimicrobial Resistance and Epigeneticsmentioning
confidence: 99%